Fibromatous Uterus in a 16-Year-Old Girl: A Case Report - Athina C. Tsili; Ekaterini D. Lentoudi; Maria I. Argyropoulou; Nikolaos Dalkalitsis; Anna Batistatou; Evangelos Paraskevaidis; Konstantine Tsampoulas (Case Reports in Medicine)
Although uterine leiomyomas are the most common neoplasms of the female genital tract, this is not the case when referring to women under the age of 20. Only a few cases of uterus leiomyomas have been reported in this age. Preoperative imaging evaluation is mandatory in adolescent women for the accurate detection, localization, and characterization of uterus leiomyomas. We report a case of a 16-year-old girl admitted to our hospital for pain and abdominal distention. The patient underwent multidetector CT examination of the abdomen and MR examination of the pelvis. Both imaging modalities revealed uterine enlargement and the presence of innumerable variably sized leiomyomas. Histopathologic examination following exploratory laparotomy confirmed the presence of uterus leiomyomas. The patient underwent laparoscopic myomectomy two years after the first operation, following MR examination of the pelvis.